2022
DOI: 10.1177/03057356221084368
|View full text |Cite
|
Sign up to set email alerts
|

Musical interaction in music therapy for depression treatment

Abstract: Music therapy is efficacious for the treatment of depression. Compared to other psychotherapeutic forms, it allows for the emergence of various modes of mutual interaction, thus enabling multiple channels for emotional expression and fostering therapeutic alliance. Although musical interaction patterns between client and therapist have been regarded as predictors of therapeutic outcome in depression, this has not yet been systematically investigated. We aim to address this gap by analyzing the possible linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This resonates also with Stensæth (2017), who stated that responsiveness in MT improvisation comprises not only meaningfulness and harmony but also struggle, dispute, and misunderstandings (p.14). Previous empirical studies have tended to operationalize the strength of interactivity between therapists and clients in terms of similarity in musical features (e.g., rhythmic similarity or synchrony) rather than contrast (e.g., Foubert et al, 2017, Hartmann et al, 2023). Our findings suggest that the highest levels of intersubjectivity are characterized by more complex musical relationships where some features converge and others diverge, as the participant and therapist find ways to complement each other's playing.…”
Section: Interim Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This resonates also with Stensæth (2017), who stated that responsiveness in MT improvisation comprises not only meaningfulness and harmony but also struggle, dispute, and misunderstandings (p.14). Previous empirical studies have tended to operationalize the strength of interactivity between therapists and clients in terms of similarity in musical features (e.g., rhythmic similarity or synchrony) rather than contrast (e.g., Foubert et al, 2017, Hartmann et al, 2023). Our findings suggest that the highest levels of intersubjectivity are characterized by more complex musical relationships where some features converge and others diverge, as the participant and therapist find ways to complement each other's playing.…”
Section: Interim Discussionmentioning
confidence: 99%
“…We did not make any constraints on the therapists' playing in the current study, and P-T pairs tended to move in and out of periods of temporal regularity (as can be seen in Figures 15 and 17 from the case studies). Various measures relating to pitch have also been used in other studies, including melodic range, pitch entropy, pitch recurrence, and the number of unique notes, among others (Hartmann et al, 2023). Several of these could be integrated into future analyses of partner-play improvisations for a more comprehensive look at how players interact musically.…”
Section: Imitation and Conflict In Musical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Music therapy using the five elements: TCM encompasses the five elements of music therapy, a treatment modality rooted in traditional Chinese music and influenced by the philosophical concepts of Yin Yang and the five elements. The five musical tones, namely Jiao, Zhi, Gong, Shang, and Yu, symbolically correspond to the five internal organs, namely the liver, heart, spleen, lung, and kidney, as well as the five associated emotions, namely anger, joy, anxiety, concern, and fear[ 25 ]. By balancing the Yin and Yang energies and regulating the circulation of Qi and blood within the human body, this practice has various functions.…”
Section: Overview Of Tcmmentioning
confidence: 99%
“…There is little research on clienttherapist musical interaction, particularly in treating depression, although many studies have examined client and/or therapist musical characteristics. 95 A review of current research on music therapy and substance abuse treatment guided an experimental receptive music therapy study that looked at correlations between music taste and diagnoses among children and teens receiving substance abuse treatment and found that music helped them feel relaxed, escape reality, and lift their mood. According to studies on active music therapy, activities like drumming, improvising, performing to music, and playing musical games might reduce depression symptoms by increasing relaxation, comfort, and healthy physiological changes.…”
Section: Music Therapymentioning
confidence: 99%